Actas Alexander: la extracción de la información (ING) - Dörries, Esteban (2004)
After a description of the historical process of demarcation of the northern border of Costa Rica, the data in the so called “Actas Alexander” (Alexander Dockets) is described in detail and possible criteria of comparison with the physical border reality is also explained. It is then followed by a description of the problems that appeared in the extraction of data and its characterization. The diverse mathematical and cartographic tools allowed to obtain, collate and to define the validity of the information.